2008
DOI: 10.1007/s11274-008-9915-z
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of xylanases from Thermomyces lanuginosus and its mutant derivative possessing novel kinetic and thermodynamic properties

Abstract: Xylanases produced from a locally isolated strain of Thermomyces lanuginosus and its mutant derivative were purified to a yield of 39.1 and 42.83% with specific activities of 15,501 and 17,778 IU mg -1 protein, respectively. The purification consisted of two steps i.e., ammonium sulphate precipitation, and gel filtration chromatography. The mutant enzyme showed high affinity for substrate, with a K m of 0.098 mg ml -1 as compared to wild type enzyme showing K m of not less than 0.112 mg ml -1 . It was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
0
20
1
1
Order By: Relevance
“…Turnover number and catalytic efficiency values of xylanase suggested that enzyme hydrolyses birchwood xylan more effectively than oat spelt xylan. Gibbs free energy (DG*), enthalpy (DH*), entropy (DS*), Gibbs free energy demands for transition state stabilization (DG Ã EÀT ) and substrate binding (DG Ã EÀS ) were lower for birchwood than those were needed for oat spelt xylan hydrolysis (Table 2) but comparable with those of xylanase derived from a thermophilic culture of Thermomyces lanuginosus (Bokhari et al 2009). …”
Section: Substrate Specificity and Kinetic Parameters Of Xylanasementioning
confidence: 92%
See 2 more Smart Citations
“…Turnover number and catalytic efficiency values of xylanase suggested that enzyme hydrolyses birchwood xylan more effectively than oat spelt xylan. Gibbs free energy (DG*), enthalpy (DH*), entropy (DS*), Gibbs free energy demands for transition state stabilization (DG Ã EÀT ) and substrate binding (DG Ã EÀS ) were lower for birchwood than those were needed for oat spelt xylan hydrolysis (Table 2) but comparable with those of xylanase derived from a thermophilic culture of Thermomyces lanuginosus (Bokhari et al 2009). …”
Section: Substrate Specificity and Kinetic Parameters Of Xylanasementioning
confidence: 92%
“…All other related enzyme activities were determined as described previously (Ghose 1987). The kinetic parameters of purified xylanase such as K m , V max , K cat and K cat /K m , were determined against xylan using concentration range of 0.5-10 mg/ml under optimized assay conditions as described previously (Bokhari et al 2009). …”
Section: Substrate Specificity and Kinetic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Xylanase precipitation with ammonium sulfate as an initial purification step was also described in the literature with recoveries varying from 59 to 72%: Bokhari et al (2009) purified xylanases produced from a strain of Thermomyces lanuginosus and its mutant by using a sequence of two steps: an overnight ammonium sulfate precipitation with 30-40% saturation at 0°C (which resulted in recovery yields of 69.80 and 71.64%) and gel filtration chromatography. Purification of xylanases from Streptomyces cyaneus using precipitation up to 60% saturated ammonium sulfate left overnight at 4°C, followed by ion exchange chromatography was also described by Ninawa et al (2008).…”
Section: Precipitation With Ammonium Sulfatementioning
confidence: 99%
“…However, most of them describe the precipitation step at a single specific condition (Bokhari et al, 2009;Li et al, 2009;Jabbar et al, 2008;Ninawa et al, 2008;Saha, 2004;Oikawa et al, 1997). Finding the optimum operational condition for precipitation can involve a study of different variables such as the type and concentration of the precipitant agent, temperature, aging time, agitation, pH and so forth.…”
Section: Introductionmentioning
confidence: 99%